The Closing of the LSU Chemistry Library. - William W. Armstrong (Issues in Science and Technology Librarianship)
Chemistry libraries are in transition these days. There are a variety of reasons, results, and end stages for these transitions. I discuss the specifics of one such transition resulting from the decision to close the LSU Chemistry Library in the Spring of 2005. I will further discuss the reasons for the move, the logistics and practicalities involved in effecting the move, and some of the pros and cons resulting from the change along with the challenges that lie ahead. [ABSTRACT FROM AUTHOR]